A qualitative study-Patient experience of tactile massage after stroke - Berit Seiger Cronfalk; Elisabet Åkesson; Jill Nygren; Anita Nyström; Anna‐My Strandell; Jorge Ruas; Mia vonEuler (Wiley, 2020)
Abstract Aim The aim was to evaluate emotional experiences of gentle skin massage, combined with regular rehabilitation in patients shortly after being diagnosed with stroke. Design A randomized study with two groups: standard individualized rehabilitation and tactile massage for 20 min three times per week (max nine times) or individual standardized rehabilitations. Methods This study applied a qualitative approach using semi‐structured questions to evaluate experiences of receiving tactile massage among patients with first‐time‐ever stroke. The interviews lasted between 6-25 min and analysed using manifest content analysis. Data was collected between 2015‐2017. This study applies to the COREQ checklist. Results Eight patients >18 years of age participated. The participants experienced emotional worries especially during the night hours affecting their sleep negatively. Receiving tactile massage was reported to relax and to ease worries and anxiety momentarily, during the session and for a longer period. The results also show that physical touch generates feelings of closeness. The findings will be presented in two categories: Human touch and The future.